The Key to Future Industrial Transformation : CAD - Ak, Çınar Akın; Efe, Ömer Faruk; Altun, Koray (Fevzullah TEMURTAŞ, 2024)
This study examines the role and impact of computer-aided design (CAD) in industrial transformation. It highlights how CAD systems provide flexibility and freedom compared to traditional methods, offering functionality across a broad spectrum from product design to prototype production. The study emphasizes that CAD is more than just a tool; it serves as a driver of innovation and competitive advantage and details its applications across various industrial sectors. Additionally, it uses the design and analysis of a bus superstructure as an example to illustrate the advantages and potential of leading CAD systems, aiming to help readers better understand CAD’s capabilities and how to apply them in their professional fields

Bu çalışma, bilgisayar destekli tasarımın (CAD) endüstriyel dönüşümdeki rolünü ve etkilerini inceler. CAD sistemlerinin geleneksel yöntemlere göre sağladığı esneklik ve özgürlüğü vurgular, ürün tasarımından prototip üretimine kadar geniş bir yelpazede işlevsellik sunduğunu belirtir. CAD’in bir araç olmaktan öte, inovasyon ve rekabet gücü sağladığına dikkat çeker ve farklı endüstriyel sektörlerdeki kullanım alanlarını detaylandırır. Ayrıca, CAD ile bir otobüs üst yapısının tasarımını ve analizini örnek olarak ele alarak, önde gelen CAD sistemlerinin avantajlarını ve potansiyelini anlamalarına yardımcı olmayı amaçlar.
Geleceğin Endüstriyel Dönüşümünün Anahtarı : CAD
Keywords: Information Systems (Other); Bilgi Sistemleri (Diğer) [EN] High Performance Computing; Yüksek Performanslı Hesaplama [EN] Machine Learning (Other); Makine Öğrenme (Diğer)